O ensino de recursos coesivos para textos dissertativos-argumentativos do ENEM - Nascimento, Tiago Antonio (2018)
The writing of the National High School Examination in recent years has become a concern for students and schools across the country. However, with the work in public institutions, difficulties were perceived with aspects that give textuality to a text, among them the mechanisms of cohesion. In this way, the research aimed to confirm if this situation was indeed present in the classroom. In order to do so, the theoretical basis of teaching in Brazilian schools was raised. In the perspective of Sociointeractionism, the study of the discursive genres and their school applicability through the didactic sequences led to organize the research method of this work. In addition, it is important to clarify the characteristics of the essay-argumentative texts, which are requested in the Writing Proposals of the exam. Finally, the definition and types of cohesive mechanisms were shown, so that it was better defined and found what was in the textual productions. Through the sequence already described, we developed the information gathering that supported our questioning with students of the last grade of High School. Through them we understand that in fact there are problems in texts written by students, not only from a cohesive point of view, but also from other aspects of textuality, such as the use of cultured norm and the construction of arguments, although they can make an argument. In this way, another didactic sequence was elaborated for a pedagogical work that is able to overcome the presented problems and that has the argumentative essay-like genre as final result, preparing for the National High School Exam, initially, and other social situations that need to be argued. However, it was understood that studies to improve the teaching of different argumentative genres and cohesion are necessary, since they are important for forming active citizens also through writing.